Natural Theology and its Relevance to Religious Pluralism in Indonesia - Kristanto, David; Runtuwene, Daniel; Lawalata, Mozes; Poroe, Herman (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
Natural theology is an underdeveloped theological theme in the recent Indonesian theological scholarship. That fact is unfortunate considering the significance of the topic to the context of religious pluralism in Indonesia. Natural theology is interdisciplinary and interreligious in nature; thus, it might open scholarly discussion for scholars from many disciplines with diverse religious backgrounds. Using a systematic theology approach, this articleargues that developing natural theology could keep balance for Christian emphasis on general and special revelation that might lead toward the enrichment of the Christian faith.